A Historical Review of China-U.S. Cooperation in Space: Launching Commercial Satellites and Technology Transfer, 1978–2000. (November 2019) - Zhang, Zhihui; Seely, Bruce
Abstract: Space collaboration has become quite common in recent years, thanks in large part to the high cost of such endeavors. This article reviews a rather early example of space collaboration, the partnership between China and the United States (U.S.) during the period 1978–2000. The collaboration began with general discussions and grew to include the use of Chinese rockets to launch U.S. satellites into orbit. We discuss where this collaboration worked successfully, where it did not, and why it ended. The ultimate collapse of the collaboration highlights the complexity of joint international projects for the factors that caused failure included the Cold War dynamic of geopolitical competition for international military and economic dominance and its continuance into the 1990s in Sino-U.S. relations; the domestic political landscape in both countries, which included bitter Democratic-Republican party rivalries in the U.S. and the top-down centralized decision-making system in China with significant influence by the People's Liberation Army; and the economic interests of U.S. aerospace contractors. But the issue that most directly ended cooperation in space was U.S. concerns about the transfer to China of sensitive satellite and rocket technology. For this history, we draw upon existing English language materials and Chinese language sources that have not been available to English-speaking scholars to illuminate China's involvement in this collaboration. We also describe subsequent Chinese space activities to pursue additional collaboration and offer comments about possible future Sino-U.S. space cooperation, against this backdrop of long-running national security concerns about transfers of knowledge and technology.